Social and Psychological Impacts of SMS Texting on Malaysian University Students - Andrew, Yau-hau Tse (2011)
Short Message Service (SMS) texting is widely used in this technological era, which has led to the questioning of the social and psychological effects of this communication medium. The objective of this study is to investigate the social and psychological influence on using SMS texts among university students in Malaysia. A sample of 971 respondents completed the online questionnaire. The findings indicated that there was a clear distinction between ‘Texters’ (=those who prefer texting) and ‘Talkers’ (=those who prefer talking) in their way of using their mobile phones and their underlying incentives. The recommendation is to design a social interface to support the interconnectivity between texters whereby people can check the status of one’s ‘textmates’, who is busy, and who is texting who. To conclude, many people own a mobile phone but they are not using their phones in the same way since people have different personalities and needs.